Phytochemical Analysis of Neem toddy collected from an old Neem tree - Sathiyaseelan, V.; Milano Prasad, V.; Velauthamurty, K. (University of Colombo, 2024)
Plants are the main source of human diet and health. The nutritional value of plants have been discussed in many literatures but there are only few research was done to find their biologically active compounds, known as phytochemicals. Among all medicinal plants, Neem tree (Azadirecta indica) is considered to be one of the most important plant containing the richest source of phytochemicals. All parts of Neem tree has medicinal value. Every different part of the Neem tree has different phytochemicals accordingly has different organoleptic characters and therapeutic value. Neem exudate/ toddy is a milky white liquid with a strong smell secreted from the angle between the 2 main branches from old trees. It is an important therapeutic agent, a rare medicine. Neem Toddy is refreshing, nutrient, and alternative tonic. It is used in some chronic and long standing cases of leprosy and other skin diseases, atopic dyspepsia and general debility. According to Siddha system of medicine it increase appetite and gives strength to body. Neem Toddy is used in chronic fever, venereal diseases and other vata related conditions. The objective of the present study was to screen the different phytochemicals present in Neem toddy. It was collected from an approximately 80 years old Neem tree in June 2024 at Point Pedro, Jaffna District during our field visit. Then the toddy was sent to laboratory, Department of chemistry, University of Jaffna, for phytochemical analysis. Toddy was tested for phytochemicals like alkaloids, flavonoids, phenolic compounds, tannin, glycoside, saponins, terpenoids, reducing sugar, protein and steroids using different test methods for qualitative analysis. The test result revealed that the toddy contain phytochemicals like alkaloids, flavonoids, phenolic compounds, tannin, glycoside, reducing sugar and protein. The results shows that the presence of many beneficial phytochemicals justifies its therapeutic action.
Keywords: Phytochemical Analysis; Neem Toddy